Hypophosphatemia in people with HIV: no benefit when switching from tenofovir disoproxil fumarate to tenfovir alafenamide. (15th July 2021) - Sandmann, Lisa; Stoll, Matthias; Behrens, Georg M.N.
Abstract : N/A: Treatment with tenofovir disoproxil fumarate (TDF) has been associated with hypophosphatemia mainly because of injury of the renal proximal tubulus. Studies on the impact of tenfovir alafenamide (TAF) on phosphate homeostasis in people with HIV (PWH) are limited. Prompted by a patient with phosphate wasting under tenofovir but no other evidence for tubular dysfunction, a retrospective cohort analysis with 102 PWH revealed that hypophosphatemia remained largely unchanged after switching from TDF to TAF.